WYBRANE PRZEJAWY OKULTYZMU W ŚWIADOMOŚCI STUDENTÓW Z PSW W BIAŁEJ PODLASKIEJ. BADANIE PILOTAŻOWE - Derlukiewicz, Aleksandra (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Occultism is the combination of esoteric doctrines that presuppose the existence of the secret forces in man and in nature. As a distinct stream of thoughts, it arose in the nineteenth century, in the era of the so-called “Fin de siècle” and it was the result of the collapse of the theocratic system and the image change of the world and man. Today, the new type of spiritual sensitivity and openness to transcendence is noticed by the younger generation. The lack of spiritual direction in solving existential crises, fear of independence, temporariness, society pressure lead young people to refer to the occult powers that give them a sense of security. The “occult revival” can be observed nowadays. The analysis shows the need for further research in the aspect, that the mass culture and promoted by the media secret (divination, clairvoyance, horoscopes) knowledge causes the revival of old practices and occult rituals among young people.